Transcriptomic analysis reveals pronounced changes in gene expression due to sub-lethal pyrethroid exposure and ageing in insecticide resistance Anopheles coluzzii - Ingham, Victoria; Brown, Faye Victoria; Ranson, Haley (BMC genomics, 2021)
Malaria control is heavily reliant on the use of insecticides that target and kill the adult female Anopheline vector. The intensive use of insecticides of the pyrethroid class has led to widespread resistance in mosquito populations. The intensity of pyrethroid resistance in some settings in Africa means mosquitoes can contact bednets treated with this insecticide class multiple times with minimal mortality effects. Furthermore, both ageing and diel cycle have been shown to have large impacts on the resistance phenotype. Together, these traits may affect other aspects of vector biology controlling the vectorial capacity or fitness of the mosquito.
Gesehen am 18.06.2021